Incidence of Palatal Fistula after One-Stage Palatoplasty and Factors Influencing the Fistula Occurrence - Vityadewi, Nurardhilah; Bangun, Kristaninta (Lingkar Studi Bedah Plastik Foundation, 2013)
Background: Cleft palate repair may be compromised by a number of complications, most commonly the development of a fistula. Fistulas are related to an increased rate of hypernasal speech, articulation problems, and food or liquid regurgitation from the nose. Fistulas also tend to recur after a secondary repair to address the fistulas. This study reviews the rate of fistula in our craniofacial center after a onestage cleft palate repair; and to determine whether, cleft type, age at repair, type of cleft repair, hemoglobin level presurgery, and patients nutritional state influence the risk of fistula occurence. Patient and Method: A retrospective analysis was performed on medical records of 93 patients who underwent palate repair between January 2012 to October 2013. All consecutive cleft (lip and) palate patients are included. Bivariate analysis was performed to identify the predictors of fistula formation. Result: Ninety-three patients (50 male and 43 female) underwent one-stage palatoplasty. Cleft palate fistulas occured in 19 of 93 patients (20,4%). The age of the patients at the time of repair ranged from 9 to 144 months (mode 18 months). All palate repairs were done in one stage, using either the two flap (N=66), Wardill-Kilner (N=24), Furlow (N=2), and Langenback (N=1) techniques. No significant influence was found related between age at the time of repair (p 0.789), body weight (p 0.725), Hemoglobin value (p 0.295), and type of cleft (p 0.249) to the rate of fistula occurrence. Summary: This study found no association between , body weight, preoperative hemoglobin value, and the type of cleft to the rate of fistula following cleft palate surgery.